Pengaruh Model Pembelajaran Problem Based Learning Bermuatan Nilai Karakter Bangsa Terhadap SIkap Demokrasi Siswa di Sekolah Dasar - Komang Novita Sri Rahayu; Desak Ketut Alit Suarnadi (STAHN Mpu Kuturan Singaraja, 2022)
National character education is carried out through the education of values and virtues which are the basic values of culture and national character. The virtue that is an attribute of a character is basically a value. Therefore, cultural education and national character are basically the development of values derived from the Indonesian nation's view of life or ideology, religion, culture, and values formulated in the goals of national education. The process of developing the values that form the basis of the character requires a continuous process, carried out through various subjects in the curriculum (citizenship, history, geography, economics, sociology, anthropology, Indonesian language, social studies, science, mathematics, religion, physical education and sports, arts and skills).